The effect of portulaca oleracea alkaloids on antidiabetic properties through changes in ceramide metabolism. Issue 1 (1st January 2021) - roozi, Hanie; Akbar Boojar, Masuod Mashhadi; Eidi, Akram; Khavari-Nejad, Ramezanali
ABSTRACT: Diabetes mellitus is the most common metabolic disease. Ceramide pathway is a vital intracellular signal transmission factor, and it has been regarded as a mediator to the development of diabetes. In the present study, the effects of OL-E and OL-L alkaloids in Portulaca oleracea are examined concerning ceramide generation and ceramide metabolizing enzymes. The beta-TC-6 pancreatic cell line was treated with various concentrations of OL-E and OL-L. cell viability, insulin secretion, glucose reuptake, Pentosidine level, total cellular ceramide and the activities of acid ceramidase (AC), neutral sphingomyelinase (NS) and glucosylceramide synthase (GCS) assayed with spectrophotometry and fluorescence evaluation. OL-E was more potent than OL-L, with the highest insulin secretion of 100 μM. Increased cytotoxicity and glycation index appeared at concentrations of 200 μM and higher. Higher concentrations of studied compounds were associated with ceramide accumulation, NS activation, and AC and GCS suppression . These findings indicated that the consentration greater than 100 µM might be involved in improving glucose homeostasis. Based on insulin secretion and glucose uptake, high concentrations of investigated compounds are correlated with ceramide generation, and this event could attenuate the Oleracein hypoglycemic effect.